Evaluation of the Use Off Label Drugs At the Obstetrics and Gynecology Polyclinic at Bandung Private General Hospital - Rahayu, Susi Afrianti; Santika, Nita (International Journal of Global Operations Research, 2024)
Off label drugs are drugs outside the indications listed on the label or outside the approval by the authorized institution. This research is a non-experimental type of research that is presented in a quantitative descriptive manner with retrospective data collection. The research sample is the same as the population (total sampling), namely all prescriptions containing off label drugs from an obstetrics and gynecology polyclinic at a private public hospital in Bandung district from May to August 2021. The purpose of the study was to evaluate the use of off label drugs in the indication category based on age, domicile, the type and use of off label drugs. The data obtained from this study were 154 drug users. off label, based on the age range of adolescents 27 (18%), adults 111 (72%), middle 16 (10%), while based on domicile most of the patients came from Baleendah sub-district 37 (24%). The types of drugs used were Mefenamic Acid 38%, Dexamethasone 3%, Metformin 12%, Misoprostol 23%, Nifedipine 8% and Ondansetron 16%. Patients using off label drugs are more common in adults with the drug used is mefenamic acid.